Utilização de ácido elágico e derivados como marcadores para a validação química de Mouriri elliptica Martius como insumo farmacêutico ativo vegetal - Silva, Gabriela Trindade de Souza e [UNIFESP] (2017)
Validated by folk medicine in ulcers and gastritis treatment, the “croadinha” (Mouriri elliptica) leaves are use as tea. This therapeutic action and it´s efficacy and safety was confirmed by preliminary studies highlighting this species as a potential treatment to peptic disease. However, it’s necessary to establish parameters to guide the production of effective and safe herbal medicine from this species. The chemical study conducted by Andreo (2008), showed the presence of tannins, flavonoids and triterpenes in active extracts. This study was conducted aiming increase the chemical knowledge of this species, to achieve it, was proceed the isolation, chemical characterization, and the development of methodology to quantify ellagic acid derivatives (phytochemical marker) present in the leaves and extracts from M. elliptica. Hydroalcoholic extracts were obtained from the leaves of M. elliptica by maceration and fractionated on Sephadex (LH-20), solid phase extraction with modified silica (C-18) and high performance liquid chromatography (HPLC) with UV detection in preparative mode. The methodology developed allowed the isolation of 7 ellagic acid derivatives. The derivatives structural determination was conducted using UV spectrophotometry and mass spectrometry. Using ellagic acid as a standard, the methodology developed and validated partially for quantification in CLAE-DAD, allowed the determination of 375 μg/g substances concentration in dry leaves of M. elliptica.